Detection of avian influenza virus in the alien invasive African sacred ibis (Threskiornis aethiopicus) in Italy - Mariacher, Alessia; Di Nicola, Matteo Riccardo; Senese, Matteo; Mariottini, Francesco; Maestrini, Michela; Bellagamba, Federica; Donnini, Carla; Capecci, Alessio; Salomoni, Angela; Varotto, Maria; Terregino, Calogero; Cersini, Antonella; et al. (Frontiers in Veterinary Science, 2025)
The African sacred ibis (Threskiornis aethiopicus), a non-native bird species in Europe, has rapidly expanded its range in Italy, prompting the adoption of national control measures due to ecological and epidemiological concerns. As part of this management plan, 20 ibises were culled in February 2025 in Tuscany (Central Italy), and tested for pathogens relevant to wildlife and public health. RT-PCR and molecular analyses on tracheal and cloacal swabs, revealed the presence of low pathogenic avian influenza virus (LPAIV) subtype H5N2 in 1 out of 20 specimens. Phylogenetic analysis showed that the virus was closely related to recent European LPAIV strains, with the PA gene segment clustered with Asian and Russian isolates from 2021–2022. Two mammalian adaptation markers (S155N and T156A) were identified in the HA protein. Although the detected strain poses minimal zoonotic risk, its presence in a highly adaptable invasive species, raises concerns about the potential role of T. aethiopicus as a bridge host in avian influenza transmission cycles. Given the increasing overlap between this species and poultry farming areas, and its scavenging behavior, continued surveillance is essential to assess its epidemiological role. Targeted control actions may be crucial in preventing the establishment of novel wildlife reservoirs and limiting viral evolution towards highly pathogenic forms. Surveillance of alien invasive species should be integrated into broader avian influenza monitoring strategies to protect public health and agricultural biosecurity.